The Historical Evolution and Preservation of Semende Kuntau Martial Art in South Sumatra - Anora Rezky Mulia; Dedi Irwanto; Risa Marta Yati (JESS (Journal of Educational Social Studies), 2026)
This study examines the history and development of the Semende Kuntau martial art in Muara Enim Regency, South Sumatra. Semende Kuntau is a form of local cultural heritage that serves not only as a martial art but also as a medium for transmitting cultural, moral, and religious values from one generation to the next. This study aims to examine the historical development, social functions, and preservation efforts of Semende Kuntau in the face of modernization. The research employed the historical research method by utilizing written sources and oral sources obtained through interviews with community leaders and Kuntau practitioners. The findings indicate that Semende Kuntau has existed since the eighteenth century and was initially transmitted through certain family lineages before gradually becoming an integral part of the community's customary and cultural activities. Over time, its function shifted from a means of self-defense to a traditional performance art presented during customary ceremonies, particularly wedding celebrations. Modernization has contributed to a decline in young people's interest in learning Kuntau. However, since 2010, various preservation efforts have been undertaken through the establishment of martial arts schools, regular training programs, and participation in cultural events. Therefore, Semende Kuntau continues to survive as an important cultural identity of the Semende community, possessing significant historical and philosophical values.